Development of Physics Teaching Modules Oriented to Scientific Approach to Improve Students' Science Process Skills - Putri Chusnul Chotimah L.; Helmi; Kaharuddin Arafah (Postgraduate, University of Mataram, 2024)
This research is a development researchs. The aim is to produce a physics teaching module oriented to a scientific approach. This teaching module is used to improve students' science process skills. The subjects of the research trial were 34 students of class X of SMAN 13 Makassar. The development model of the physics teaching module oriented to a scientific approach is a 4-D instructional model consisting of define, design, development, dissemination. The research instrument used a validation sheet, a practitioner assessment questionnaire, and a science process skills test instrument. Based on the results of the data analysis, the following conclusions were obtained: the physics teaching module oriented to a scientific approach was declared valid and feasible to use with an integrated scientific approach learning activity structure and a collection of questions according to the science process skills indicators; the physics teaching module oriented to a scientific approach reviewed from the assessment of practitioners, namely physics subject teachers, was in the very good category; the effectiveness of the physics teaching module oriented to a scientific approach reviewed from students' science process skills using the N-Gain score was in the effective category. This can be interpreted that the physics teaching module oriented to a scientific approach that was developed is effective in improving students' science process skills.